KAPITALISASI KELUARGA PENDOPO DALAM PEMASARAN POLITIK PARTAI NASDEM PADA PEMILU LEGISLATIF 2019 DI KABUPATEN BLORA - Ishartono, Ilham -; -, Turtiantoro - (Journal of Politic and Government Studies, 2020)
The Nasdem Party is a party that experienced a significant increase in votes in the 2019 Legislative Election. This is inseparable from the Party typology that places voters as consumers as is the practice of campaigning for "Politics Without Mahar". Blora Regency's Nasdem Party carries out political marketing efforts by placing the Blora Regent and his sons in strategic party positions as a symbol of "Pendopo Families. The completeness of political capital and economic capital of the Pendopo family makes the political marketing of the Nasdem Party in Blora Regency full of capitalization on various fronts in achieving the objectives of the agreement between the Nasdem Party and the Regent. The informants in this study were members of the DPD Nasdem Party in Blora Regency and members involved in political marketing in the 2019 Legislative Election. The results of this study were aimed at describing the capitalization of the Pendopo family in playing a major role in various forms of political marketing of the Nasdem Party in Blora Regency. Strategic positions in party management, capitalizing the witness team, and establishing campaign images using serial numbers are the interests of the pendopo family led by Blora Regent Djoko Nugroho. Likewise, the factors that led to the increase in votes also came from the electability of the pendopo family's assistance in forming a voting base and had an impact on the placement of 5 legislative candidates according to the orders of the pendopo families to be able to realize parliamentary seats.